Relationship of The Role of Midwives in Prevention of Covid-19 with Mother's Anxiety in The Covid-19 Pandemic Periodat PMB Johana Widijati Village Sidorejo Kauman Tulungagung - Ernawati Tri Handayani; Dewi Ratna Sulistina (Institute of Computer Science (IOCS), 2021)
Coronavirus is still a problem in the world including Indonesia because the transmission is still happening. Many problems occurred as a result of the emergence of the Covid-19 case, including system changes that occurred suddenly and economic changes that caused anxiety in the community. This study aims to analyze the relationship between the role of midwives in preventing Covid-19 and maternal anxiety during the Covid-19 pandemic at PMB Johana Widijati, Sidorejo Village, Kauman Tulungagung. The research was conducted at PMB Johana Widijati, Sidorejo Village, Kauman Tulungagung in December 2020. The analytical research design was correlational with a cross sectional approach. The study population was all mothers who did the examination at PMB Johana Widijati Sidorejo Village, Kauman Tulungagung. The purposive sampling technique consisted of 37 people. Data analysis used Spearman rho test. Most of the respondents, namely 27 respondents (73%) stated that midwives played a role in preventing Covid-19, most of the respondents, namely 17 respondents (45.9%) did not experience anxiety during the Covid-19 pandemic and there were a small number of respondents, namely a number 5 respondents (13.5%) experienced moderate anxiety. There is a relationship between the role of midwives in preventing Covid-19 and maternal anxiety during the Covid-19 pandemic where the p value is 0.000 (<0.05).